Couture and Consensus : Fashion and Politics in Postcolonial Argentina - Root, Regina A. (Book collections on Project MUSE., 2010)
Following Argentina's revolution in 1810, the dress of young patriots inspired a nation and distanced its politics from the relics of Spanish colonialism. Fashion writing often escaped the notice of authorities, allowing authors to masquerade political ideas under the guise of frivolity and entertainment. In Couture and Consensus, Regina A. Root maps this pivotal and overlooked facet of Argentine cultural history, showing how politics emerged from dress to disrupt authoritarian practices and stimulate creativity in a newly independent nation.